Effectiveness of Eco Enzymes in Reducing Chemical Parameters of Tofu Factory Liquid Waste in Klumutan Village, Saradan District - Melisa Cahyaning Putri; Retno Widiarini; Karina Nur Ramadanintyas (International Journal Labs, 2024)
The tofu industry generates substantial liquid waste that poses environmental challenges due to its high chemical oxygen demand (COD), total suspended solids (TSS), and pH levels. This study aimed to determine the effectiveness of Eco Enzymes in reducing these chemical parameters in the tofu industry waste in Klumutan Village, Saradan District. Utilizing a Quasi-Experimental method, the research employed purposive sampling of liquid waste from tofu production. The findings revealed that the application of Ecoenzyme at doses of 5%, 10%, and 15%, with detention times of 10, 15, and 20 days, significantly reduced COD, TSS, and pH levels. The results showed that both the dosage and detention time had a substantial impact on the effectiveness of Ecoenzyme in treating the waste. The implications of this study suggest that Eco Enzymes can be an effective, eco-friendly solution for improving wastewater management in the tofu industry, thereby contributing to environmental sustainability.